Hidroxiapatitas dopadas com Zn(II) e decoradas com óxido de zinco como agentes antimicrobianos, adsorventes para tetraciclina e pigmentos híbridos - Lima, Cleibson Oliveira de (2021)
Hydroxyapatite (HAp) is an inorganic material, the structure of which allows different types of modifications, such as doping and surface functionalization. This can promote changes in the physical and chemical properties of HAp, leading to an improvement of its applications. In this context, doping HAp with Zn²+ cations and/or decorating the HAp surface with zinc oxide (ZnO) nanoparticles were carried out in order to obtain new materials with different characteristics. For the synthesis, a combined template (casein and sucrose) and co-precipitation/microwave-assisted hydrothermal was used. The chemical reactions were performed from the hydrolysis of precursor salts of calcium nitrate, ammonium phosphate and zinc acetate/nitrate at 30 oC for 1 h under microwave heating at 80 oC for 20 min with and without templates, followed or not by calcination at 500 oC in oxidizing atmosphere. Rietveld structural refinements in combination with spectroscopic techniques (infrared spectroscopy, Raman and X-ray spectroscopy) suggested the formation of Zn-HAp/ZnO-y type materials (y = 0, 1, 2 and 3 considering the formation of 0, 5, 10 and 20 % ZnO, respectively) and Znx-HAp (x = 0; 0.5; 1.0 and 2.0 mol% of Zn²+). All the all materials presented a typical hydroxyapatite hexagonal P63/m structure. Mesoporous Zn-HAp/ZnO-y and Znx-HAp materials with specific surface area (SBET) of 52-69 m²g¹ and 138-182 m²g-¹ were synthesized using sacarose and caseine, respectively. Regarding the antibacterial activity of mesoporous materials doped with Zn2+, they showed greater efficiency when compared to the pure mesoporous sample. The maximum growth inhibition capacity of E. coli and S. aureus of 77 and 50%, respectively, was obtained using the sample Zn2%-mHAp. Decorating ZnO onto HAps played an important role in adjusting of the adsorptive capacity of the materials. Zn-HAp/ZnO-3 had the highest adsorption of 168.46 mg L-1 of tetracycline in 20 min. Finally, stable hybrid pigments were obtained from mesoporous Zn-HAp/ZnO-y materials synthesized using sucrose template and alizarin at pHs 4 and 8.5. The pigment of HAp/ZnO-2/AZ/pH8.5 showed the highest color stability after 264 h of UV light exposure. All these results demonstrate the potential of modifying hydroxyapatites in order to obtain new materials with specific properties for the use as adsorbents, hybrid pigments and antimicrobial materials.